Analisis Pengaruh Faktor-Faktor Corporate Governance Terhadap Nilai Perusahaan - Suhailah Amatullah (LPPM ISNJ Bengkalis, 2017)
The purpose of this study is to provide empirical evidence, the influence of corporate governance factors on corporate value. These factors are company size, profitability, number of members of the board of commissioners, the proposition of independent commissioners and the number of member of the audit committee. From the analysis that has been done, obtained a sample of 44 companies with 132 observation data. Data analysis using multiple regression analysis. The result of the analysis shows that public ownership, firm size, profitability, number of members of the board of commissioners, the proportion of independent commissioners, the numbers of members of the audit committee simultaneously have a significant influence on the value of the company. Partially profitability has a significant positive effect on firm value. While other variables, public ownership, firm size, number of members of the road commissioners, the proportion of independent commissioners, the number of audit committee member have influence but not significant.